THE EFFECT OF KAHOOT GAMIFICATION STRATEGY ON IMPROVING MATH COMPREHENSION IN ELEMENTARY SCHOOL STUDENTS - Putri Marlita Sari; Ratnasari Diah Utami (Jurnal Cakrawala Pendas, 2025)
Mathematics is one of the subjects that is considered difficult and less attractive, which has an impact on students' low understanding of concepts. One of the obstacles in learning is the limitation of technology, especially the unavailability of adequate computer equipment in the classroom. This condition hinders the application of interactive learning media that can increase student interest and understanding. This study aims to analyze the effect of gamification strategy using Kahoot technology on improving mathematics understanding of grade 3 elementary school students. The method used was a quasi-experiment with a quantitative approach, comparing two classes: an experimental group using Kahoot and a control group using conventional learning methods. The research was conducted in grade 3 of MI Muhammadiyah Gonilan. Data analysis included normality test, Wilcoxon test, and N-gain test. The results showed the average post-test score of the control class was 74.73 and the experimental class was 82.10. The findings show that gamification strategy using Kahoot has a positive and significant effect on improving students' math comprehension.